Garden Snail Predatory Insects’ Modus Operandi Under Laboratory Conditions - Giulia Murgia; Valentina Coroneo; Carlo Zuddas; Sara Maria Pani; Maria Paola Cogoni (Insects)
Heliciculture farms are susceptible to significant biotic issues that can impact snail breeding, among them, the entomofauna predation of snails. Predatory insects can cause damage to snail shells during predation, and sometimes, the specific type of damage may be characteristic of certain insect families or species. Under laboratory conditions, we analysed the predatory activity of the species Silpha tristis Illiger, 1798 (Coleoptera: Silphidae), Ocypus olens (Müller, 1764) (Coleoptera: Staphylinidae), Carabus (Macrothorax) morbillosus constantinus Kraatz, 1899 (Coleoptera: Carabidae), and Lampyris sardiniae Geisthardt, 1987 (Coleoptera: Lampyridae) against the gastropod Cornu aspersum (Müller, 1774) reared on snail farms located in the Sardinian region. The adult and larval stages of each species were tested, except for L. sardiniae, as only the larval stage preys upon snails. This study showed that among all of the species considered, only two insects were able to damage the shell of C. aspersum: C. morbillosus constantinus and O.olens. This may prove valuable in C. aspersum breeding for the recognition of specific lesions, even in the absence of the predator.